Effect of substitution of coconut coir waste on the compressive strength of non-structural concrete - Imam Heru Nurfais; Nur Azizah Affandy; Salwa Nabilah (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2021)
Using coconut fiber waste (LSK) in concrete mixes has good prospects because Indonesia has abundant natural resources. The addition of this fiber aims to improve the properties of concrete. This study aims to determine the effect of adding coconut fiber waste (LSK) as a substitute for coarse aggregate on the compressive strength of non-structural concrete and utilizing coconut fiber waste to reduce the accumulation of coconut waste and increase the selling value of coconut fibers. Making concrete mixtures with standard SNI 03-2834-2000, concrete compressive strength f'c 16.9 MPa concrete age 28 days, with 4 variations of the mixture, namely LSK 0%, LSK 0.5%, LSK 1%, LSK 1.5%, and LSK 2%. The test object is cylindrical with a diameter of 15 cm and a height of 30 cm, with 30 specimens. According to the findings of this study, the addition of coco fiber reduced the compressive strength of the concrete. In the compressive strength test of concrete, aged seven days and 28 days, the highest average compressive strength values of LSK 0 were 14.72 MPa and 21.62 MPa. Of the three variations of LSK, LSK 0.5 and LSK 1 are closest to normal concrete. The relationship between the uses of LSK on the compressive strength of concrete at the age of 28 days. Its effect on the decrease in compressive strength occurs in LSK 0.5, LSK 1, LSK 1.5, and LSK 2. The equation obtained from the linear regression equation y = -4.764+19.88 with a value of R2 = 0.827. The results show that the coconut fiber mixture (LSK) cannot provide a compressive strength of concrete that exceeds the compressive strength of normal concrete. Penggunaan limbah sabut kelapa (LSK) dalam campuran beton memiliki prospek yang bagus karena Indonesia memiliki sumber daya alam yang melimpah. Penambahan serat ini bertujuan untuk memperbaiki sifat-sifat beton. Penelitian ini bertujuan untuk mengetahui pengaruh penambahan limbah serat sabut kelapa (LSK) sebagai subtitusi agregat kasar terhadap kuat tekan beton non-struktural, dan memanfaatkan limbah sabut kelapa sehingga bisa mengurangi penumpukan limbah kelapa dan menambah nilai jual dari sabut kelapa. Pembuatan campuran beton dengan standar SNI 03-2834-2000, kuat tekan beton f’c 16,9 MPa usia beton 28 hari, dengan 4 variasi campuran, yaitu LSK 0%, LSK 0,5%, LSK 1%, LSK 1,5% dan LSK 2%. Benda uji berbentuk silinder dengan diameter 15 cm dan tinggi 30 cm, dengan jumlah benda uji 30 buah. Hasil dari penelitian ini adalah penambahan serat sabut kelapa mengakibatkan terjadinya penurunan kuat tekan pada beton. Pada uji kuat tekan beton umur 7 hari dan 28 hari nilai kuat tekan rata-rata tertinggi LSK 0 adalah 14,72 MPa, dan 21,62 Mpa. Dari ketiga variasi LSK, LSK 0,5 dan LSK 1 yang paling mendekati beton normalnya. Hubungan penggunaan LSK terhadap kuat tekan beton pada umur 28 hari pengaruhnya pada penurunan kuat tekan yang terjadi pada LSK 0,5, LSK 1, LSK 1,5 dan LSK 2. Persamaan yang didapat dari persamaan regresi linear y = -4,764+19,88 dengan nilai R2 = 0,827. Hal ini menunjukkan bahwa campuran sabut kelapa (LSK) tidak bisa memberikan kuat tekan beton melebihi kuat tekan beton normal.